The Evidentiary Strength of Land Ownership: A Comparison Between Written Documentation and Twenty Years of Continuous Physical Possession - Permadi, Iwan; Kusumawati, Nita (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2024)
This article analyzes the strength of written evidence and proof of physical possession in registering land rights in Indonesia. This normative juridical research examines laws and regulations related to land registration, particularly GR No. 24/1997 and GR No. 18/2021. The results show that while evidence of physical possession for 20 consecutive years can be the basis for land registration, written evidence tends to have stronger evidentiary power in dispute resolution. However, the Indonesian legal system has no clear hierarchy between the two. Judges have an important role in assessing the evidence presented based on the principles of evidentiary law. This research recommends increased socialization on the importance of land registration and the need for a clearer policy on the hierarchy of evidence in land dispute resolution to improve legal certainty.